Congenital duplication of the superior sagittal sinus and parietal encephalocele after vacuum extraction delivery - Neumann, Jan-Oliver; Herweh, Christian; Halatsch, Marc-Eric (Acta neurochirurgica, 2010)
A newly-born infant with a congenital dural and bony defect and an associated short-segmented duplication of the superior sagittal sinus suffered from herniation and infarction of parietal brain tissue secondary to vacuum extraction. This ultimately led to the formation of a subgaleal cerebrospinal fluid (CSF) collection. Initial operative closure of the encephalocele was performed by attaching a galeal flap to the periostium surrounding the congenital defect. As the bony defect developed characteristics of a growing fracture later on, dural repair, transplantation of a split-bone flap and, finally, the insertion of a ventriculoperitoneal shunt became necessary. This case affirms that stringent indication and cautious usage of vacuum-assisted delivery is strongly recommended, especially in view of the possibility that undetected congenital cranial, vascular and/or cerebral alterations may be present.
Online veröffentlicht: 29 July 2009
Gesehen am 12.05.2023